PENGARUH PROFITABILITAS, LEVERAGE, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DIBURSA EFEK INDONESIA - MUHAMMAD LUKMAN KHAKIM,; DENY YUDIANTORO, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
The company has the goal of getting maximum profit, wants to prosper the owners or shareholders and maximize the value of the company which is reflected in its share price. The research objectives include: (1) To examine and analyze the effect of partial profitability on firm value in manufacturing companies listed on the Indonesian stock exchange. (2) To examine and analyze the effect of partial leverage on firm value in manufacturing companies listed on the Indonesian stock exchange. (3) To examine and analyze the effect of dividend policy partially on firm value in manufacturing companies listed on the Indonesian stock exchange. (4) To test and analyze the effect of profitability, leverage, and dividend policy simultaneously on firm value in manufacturing companies listed on the Indonesian stock exchange. This study uses a quantitative approach, which is used to determine the effect of profitability, leverage, and dividend policy on firm value. The analysis used is the data in the form of numbers. While the data analysis method used: (1) descriptive statistical test, (2) panel data test, (3) classical assumption test, (4) coefficient of determination, and (5) inferential statistical analysis. The results of the study show that: (1) Profitability has an effect on firm value in manufacturing companies. (2) Leverage has an effect on firm value in manufacturing companies. (3) Dividend policy has no effect on firm value in manufacturing companies. (4) Profitability, leverage, and firm value simultaneously affect firm value.